Meninos eu li!: cartas de leitores de Sagarana a Guimarães Rosa - Sousa, Maria do Rosário Abreu e (2012)
The purpose of the research Meninos eu li!: leitores de Sagarana escrevem a Guimarães Rosa (Readers of Sagarana write to Guimarães Rosa), whose corpus is composed of eighty five letters regarding the reception of the writer’s debut book, Sagarana, published in April 1946, and archived at the Institute of Brazilian Studies of the University of São Paulo, is to discuss the reading of these early readers in the light of the literary criticism. To accomplish this, the following steps were taken: 1)- identification of the main topics of each letter. 2)- Identification of the reading paradigms – authors, works, elements of literary criticism mentioned by the letters’ senders. 3)- Discussion of the literary criticism about the book in order to know its importance as a model for the community of readers composed by the letters’ writers. At a second stage, the correspondences were divided according to identity, as follows: unknown senders and female senders, with the aim to identify similarities and differences in the different ways of reading. Based on the theoretical assumptions of the Aesthetics of Reception, the History of Reading and the Epistolary Discourse, the research drew the following conclusions: 1 - the importance of the literary criticism as a mediator of reading. 2 - legitimating of Brazilian identity through literature. 3 - the strong presence of pre-modernist writers as reading paradigms both for the literary critics and for the letters’ writers. 4 - the growth and maturing of the Brazilian cultural market. 5 - the importance that both the State and the informal practices have in this market. 6 - the long period for maturation and materialization of the projects, announced in the letters, for expanding the book market circulation of Sagarana.